Kilka uwag o ryzyku prowadzenia działalności gospodarczej - Wroński, Paweł (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article presents selected definitions of risk notions and different classifications of risk connected with carrying out business activity, it also shows different kinds of risk, which enterprises from domestic and foreign' markets can encounter and points out the necessity of the introduction in today's changing environment the risk management to achieve better results in an enterprise. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 440-447